(untitled) (Journal of actual problems of jurisprudence, 2016)
The article examines the sources of Islamic law, which include: primary sources – the Qur’an and Sunnah, rational sources – «ijma» – the unanimous opinion of Muslims, «qiyas» – reasoning by analogy; «ijtihad» – creative work and interpretation of the legal and religious norms; «fatwa» - a decision the highest Muslim leaders vested appropriate authority for individual religious and legal issues, as well as positive sources, in particular, the legal customs and local traditions, which do not contradict the Muslim law.